Chems4EU: chemsex use and its impacts across four European countries in HIV‐positive men who have sex with men attending HIV services. Issue 10 (25th August 2021) - Whitlock, Gary G.; Protopapas, Konstantinos; Bernardino, Jose I.; Imaz, Arkaitz; Curran, Adrian; Stingone, Christof; Shivasankar, Sivapatham; Edwards, Sarah; Herbert, Sophie; Thomas, Konstantinos; Mican, Rafael; Prieto, Paula; et al.
Abstract: Introduction: Chemsex in a European context is the use of any of the following drugs to facilitate sex: crystal methamphetamine, mephedrone and gamma‐hydroxybutyrate (GHB)/gamma‐butyrolactone (GBL) and, to a lesser extent, cocaine and ketamine. This study describes the prevalence of self‐reported recreational drug use and chemsex in HIV‐positive men who have sex with men (MSM) accessing HIV services in four countries. It also examines the problematic impacts and harms of chemsex and access to chemsex‐related services. Methods: This is a cross‐sectional multi‐centre questionnaire study of HIV‐positive MSM accessing nine HIV services in the UK, Spain, Greece and Italy. Results: In all, 1589 HIV‐positive MSM attending HIV services in four countries completed the questionnaire. The median age of participants was 38 years (interquartile range: 32–46 years) and 1525 (96.0%) were taking antiretroviral therapy (ART). In the previous 12 months, 709 (44.6%) had used recreational drugs, 382 (24.0%) reported chemsex and 104 (6.5%) reported injection of chemsex‐associated drugs ('slamsex'). Of the 382 engaging in chemsex, 155 (40.6%) reported unwanted side effects as a result of chemsex and 81 (21.2%) as a result of withdrawal from chemsex. The reported negative impacts from chemsex were on work (25.1%, 96), friends/family (24.3%, 93) and relationships (28.3%, 108). Fifty‐seven (14.9%) accessed chemsex‐related services in the past year, 38 of whom (67%) felt the service met their needs. Discussion: A quarter of participants self‐reported chemsex in the past 12 months. There were high rates of harms from chemsex across all countries, including negative impacts on work, friends/family and relationships. Although a minority of those engaging in chemsex accessed support, most found this useful.